The distributive cycle: Evidence and current debates - Jose Barrales-Ruiz; Ivan Mendieta-Mu\~noz; Codrina Rada; Daniele Tavani; Rudiger von Arnim (The University of Utah, Department of Economics, 2020)
This paper surveys current debates on the distributive cycle. The literature builds on R.M. Goodwin's seminal 1967 chapter titled "A growth cycle." We review theoretical motivations for the distributive cycle, which, despite significant differences, all imply that macroeconomic activity leads the labor share. Subsequently, we summarize and update evidence on the existence of a distributive cycle, with a focus on the post-war US macroeconomy. We analyze activity and labor share series and their interaction in the frequency domain, and also employ standard vector autoregressions. Results confirm the distributive cycle across the entire US post-war period. We contextualize results vis-à-vis current topics, including a financial cycle, technical change and secular stagnation.
Keywords: E12; E24; E25; E32; 330; Distributive cycle; US labor share of income; neo-Goodwin